The Development of Al-Qur'an and Hadith Integrated Guided Inquiry Students’ Worksheet to Improve Students’ Learning Outcomes and Religious Character - Kumalasari, Mia; Rahayu, Enni Suwarsi; Saptono, Sigit; Parmin, Parmin (Universitas Negeri Semarang)
The development of Al-Qur'an and Hadith integrated guided inquiry student worksheets to improve students’ learning outcomes and religious character was carried out. This study aims to determine the effectiveness of Al-Qur'an and Hadith integrated guided inquiry student worksheets in Askhabul Kahfi Junior High School Semarang in the academic year 2020/2021. In this study used research and development method, then the selected class was used for research, i.e class VII D as the control class and class VII B as the experimental class, involving 32 students in the experimental class and 32 students in the control class. The normality test analysis showed that the the data for both classes were normally distributed. The calculation of the similarity test for the both posttest data variances of the two classes had the same variance. The average posttest score of the control class was 79.06 and the experimental class was 82.08. The results of the t-test analysis showed a significant difference in the mean between the experimental class and the control class. Based on the results of the data analysis on the religious character of the students, the average value of the religious aspects in the experimental class had score of 3.59 in the very good category, and the control class had score of 3.27 in the good category, so it can be concluded that the experimental class has better religious character than the control class.